2018
DOI: 10.18845/rfmk.v16i38.3991
|View full text |Cite
|
Sign up to set email alerts
|

Agricultural Wastes – A Promising Source for Biogas Production in Developing Countries of the Tropical and Subtropical Regions

Abstract: Most of the so called developing countries are located in tropical and/or sub-tropical regions whilst in contrast, most of the developed countries are in the temperate climate zones. It is expected that a huge increase in the future global energy consumption will be caused by the demand of the developing countries. Caused by the favourable climate conditions in tropical and/or sub-tropical regions the average productivity of biomass is 4 – 5 times higher than that of biomass grown in the temperate regions. Man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…Table 1 reports the FAO estimate of biowastes. Africa is located in tropical and subtropical region and due to good climate conditions; production rate of biomass is 4-5 times the other regions [14] leading to high agricultural and forest wastes. In 2012, 11.519 Gt was produced and 5.098 Gt was collected and in 2025, 28.155 Gt and 18.232 Gt are expected to be produced and collected every year [4].…”
Section: Contribution Of Energy Sources In Electricity Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 reports the FAO estimate of biowastes. Africa is located in tropical and subtropical region and due to good climate conditions; production rate of biomass is 4-5 times the other regions [14] leading to high agricultural and forest wastes. In 2012, 11.519 Gt was produced and 5.098 Gt was collected and in 2025, 28.155 Gt and 18.232 Gt are expected to be produced and collected every year [4].…”
Section: Contribution Of Energy Sources In Electricity Productionmentioning
confidence: 99%
“…These wastes can be a good source of energy if they are successfully transformed. For example, in 2019 Barz et al reported that if agricultural wastes are properly handled, they can contribute 20-40%ofprimaryenergy [14], demonstrating that all biowastes can contribute significantly. According to estimates, processing crop and agro-processing leftovers might provide 4.2 EJ in 2030, forest Residue 1.1 EJ, and animal residue 1.5 EJ.…”
Section: Contribution Of Energy Sources In Electricity Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Poor treatment of wastes that lead to pollution and loss of energy is common in developing countries. If these wastes are well treated can generate 20-40% of primary energy in developing countries [123] and if well converted can help to reduce the pressure of feedstocks for biooil and adsorption biochar production.…”
Section: Intermediate Pyrolysis As the Appropriatementioning
confidence: 99%
“…In the case of Costa Rica, there is potential of using lignocellulose residues from forestry and waste from the production of palm oil and pineapple [13]. Banana [14], rice, sugar cane and coffee waste are also potential sources of carbon [15]. Rice husk, discarded from the rice milling process, has a reported mass composition of 66.67 % carbon, 22.30 % SiO2, 7.10 % H 2 O, 0.82 Al 2 O 3 , 0.78 % Fe 2 O 3 , 1.10 % K 2 O, 0.78 % Na 2 O, 0.24 % CaO and 0.21 % MgO, this composition varies depending on the crop location and soil preparation.…”
Section: Introductionmentioning
confidence: 99%